Drug-free phototherapy of superficial tumors - Mehanna, Stephanie (2021)
Visible light has long been recognized as a treatment for many diseases and an essential component of photo-induced chemotherapy. While previous data proved its inherent cytotoxicity, this study is the first to explore the use of a commercially available, high-intensity white LED light (24.5 mW.cm−2) as a treatment for skin tumors. After a 9-h exposure in vitro, the viability of Human Malignant Melanoma cells (A375) decreased by around 70%. Western blot analysis suggested an apoptotic cell death confirmed by the upregulation of Bax, cleaved PARP/caspase-3/8, cytochrome c, and t-bid. Additionally, cellular ROS accumulation and DNA damage were induced upon irradiation with blue light. When tested on a DMBA/TPA skin carcinogenesis model, a 90-min exposure to white light thrice weekly resulted in a significant decrease in tumor volumes/incidence compared to control and cisplatin groups, and restored normal morphological features, as confirmed by histopathology. Toxicological evaluation of ight-treated animals indicated a 100% survival rate, no skin irritation, no signs of discomfort or changes in body weight/behavior, and no toxicities to vital organs. Although these results must be confirmed by further studies, this research showed that short-exposure by commercially available high-intensity white LED light irradiation may be a promising approach for the treatment of superficial malignancies.